Diagnostic Algorithmic Proposal Based on Comprehensive Immunohistochemical Evaluation of 297 Invasive Endocervical Adenocarcinomas. (August 2018) - Stolnicu, Simona; Barsan, Iulia; Hoang, Lien; Patel, Prusha; Chiriboga, Luis; Terinte, Cristina; Pesci, Anna; Aviel-Ronen, Sarit; Kiyokawa, Takako; Alvarado-Cabrero, Isabel; Pike, Malcolm C.; Oliva, Esther; et al.
Abstract : The International Endocervical Adenocarcinoma Criteria and Classification was developed to separate endocervical adenocarcinomas (ECAs) into 2 main categories on the basis of morphology such as human papilloma virus–associated (HPVA) and non-human papilloma virus–associated adenocarcinomas. We aimed to improve the diagnostic accuracy of International Endocervical Adenocarcinoma Criteria and Classification by performing a comprehensive immunohistochemical evaluation and constructing objective immunohistochemical-based algorithms for the classification of these tumors. Tissue microarrays were constructed from 297 of 409 cases used to develop the original classification. Immunostains included p16, p53, estrogen receptor (ER), progesterone receptor, androgen receptor, Vimentin, CK7, CK20, HER2, HIK1083, MUC6, CA-IX, SATB2, HNF-1beta, napsin A, PAX8, CDX2, GATA3, p63, p40, and TTF-1. High-risk human papilloma virus (HR-HPV) was detected by in situ hybridization (ISH) using probes against E6 and E7 mRNA expressed in 18 different virus types. Vimentin, ER, and progesterone receptor were expressed in a significant minority of ECAs, mostly HPVAs, limiting their use in differential diagnosis of endometrioid carcinoma when unaccompanied by HPV-ISH or p16. HR-HPV ISH had superior sensitivity, specificity, and negative and positive predictive values compared with p16, as published previously. HNF-1beta did not have the anticipated discriminatory power for clear cell carcinoma, nor did MUC6 or CA-IX for gastric-type carcinoma. HNF-1beta and napsin A were variably expressed in clear cell carcinoma, with HNF-1beta demonstrating less specificity, as it was ubiquitously expressed in gastric-type carcinoma and in the majority of HPV-associated mucinous (predominantly intestinal-type and invasive ECA resembling stratified mucin-producing intraepithelial lesion [iSMILE]) and usual-type carcinomas. HIK1083 was expressed in nearly half of gastric-type carcinomas, but not in the vast majority of other subtypes. GATA3 was positive in 10% of usual-type adenocarcinomas and in single examples of other subtypes. Rare gastric-type and HPVA mucinous carcinomas displayed HER2 overexpression. Androgen receptor was positive in 6% of usual-type adenocarcinomas. Aberrant p53 expression was found in only 3.6% of usual-type HPVA carcinomas, but it was more prevalent in mucinous (intestinal type and iSMILE) HPVAs and non-human papilloma virus–associates (particularly in gastric-type carcinoma, >50% of cases). The following diagnostic classification algorithms were developed with the above data. Carcinomas without overt cytoplasmic mucin (endometrioid, usual-type endocervical, clear cell, and mesonephric carcinomas) can be subclassified using HR-HPV ISH, ER, and GATA3, whereas carcinomas with easily appreciated cytoplasmic mucin (endometrioid carcinoma with mucinous features, HPVA mucinous, and gastric-type carcinomas) can be subclassified with HR-HPV ISH and ER.